Association between bone mineral density and lower back pain in the general United States population using the NHANES of 1999–2004 - Zhou, Yang; Li, Chi; Dai, WangYing; Teng, HongLin; Wang, Yu; Zhu, MingYu; Wang, Jing (Frontiers in Surgery, 2025)
ObjectivesLower back pain (LBP) is a prevalent health issue that has substantial effects on individuals and society. However, the association between bone mineral density (BMD) and LBP remains controversial. In this study we aimed to ascertain whether a relationship exists between BMD and LBP in the United States population.MethodsData from the National Health and Nutrition Examination Survey (NHANES) spanning 1999–2004 were analyzed using a cross-sectional approach. BMD and LBP were assessed using multivariate logistic regression, smoothing curves, and generalized additive models. Subgroup analyses were also performed to ensure data stability and mitigate confounding factors.ResultsIn this population-based study, the data of 107,570 adults were analyzed (mean age: 47.13 ± 18.38 years) and 36.74% of them had LBP. After controlling for all covariates, a positive correlation was established between BMD and LBP [odds ratio (OR) = 1.87, 95% confidence interval (CI) = (1.00, 3.50)]. The two-segment linear regression model revealed a U-shaped relationship between BMD and LBP with a 1.14 g/cm2 inflection point. BMD values <1.14 g/cm2 were linked to a lower likelihood of experiencing LBP [OR = 0.55, 95% CI = (0.45, 0.68)]. However, a BMD >1.14 g/cm2 increased the risk of LBP [OR = 6.15, 95% CI = (4.51, 8.39)].ConclusionsBMP was significantly and positively correlated with LBP. A U-shaped relationship was observed between BMD and LBP, indicating that both insufficient and excessive BMD may increase the risk of LBP.